Спрощення структури нечіткого регулятора для керування ВРД - Лозинський, Андрій Орестович; Михайлович, Тарас Ігорович (НТУ "ХПІ", 2010)
A new method for fuzzy-controller’s synthesis of sensorless SRM is proposed. Synthesis of separate controller-blocks has been described. The system's behavior in different operating modes has been researched.
Fuzzy-controller`s structure simplification for control of the switched reluctance motor
Keywords: двигун вентильний; двигун реактивний; електропривід; буфер енергії; напруга; живлення; фаззі-регулятор; ротор